PAYLATER AND FLASHSALE ON CONSUMPTIVE BEHAVIOR OF SHOPEE FROM ISLAMIC ECONOMICS PERSPECTIVE - Rismawati, Rismawati; Syaharuddin, Syaharuddin; Supriadi, Supriadi; Sudirman, Sudirman; Arsyad, Kamaruddin (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
The purpose of writing this article is to determine the effect of the paylater system and flashsale promo on the consumer behavior of Shopee marketplace users from an Islamic Economics perspective on students of the Faculty of Da'wah and Communication. Seeing the phenomenon of the use of paylater and flashsale promos that are increasingly used, it raises curiosity whether these two features are in accordance with Islamic economic principles. This article uses a descriptive analysis research method, namely describing the understanding of the paylater system and flashsale promos, on consumer behavior in the Islamic economic perspective. While the type of research in this article is research with an associative approach that aims to ask about the relationship between two or more variables. The results of this study suggest that from an Islamic economic perspective, consumer behavior caused by the paylater system and flashsale promos by buying products excessively is not in line with the principles of Islamic economics which prioritize maslahah or usefulness compared to (utility) material satisfaction alone. Moreover, the element of additional costs due to late payments from paylater is prohibited because it is usury. The author's suggestion is that further studies can explore how consumer behavior due to paylater and flash sales impacts economic, social, and environmental sustainability, as well as how Islamic economics can provide sustainability-oriented solutions.